KEEFEKTIFAN PELAKSANAAN PROGRAM PEKARANGAN PANGAN LESTARI (P2L) DI KWT JATI MANDIRI DESA KEBAN JATI KECAMATAN ULU MANNA – BENGKULU SELATAN - Emlan Fauzi; Tri Susanto; Ahmad Damiri; Jhon Firison; Harwi Kusnadi; Andi Ishak (Politeknik Pembangunan Pertanian Medan, 2022)
The use of the yard has been carried out by KWT members but has not been optimally organized and business-oriented. This study aims to determine the effectiveness of the sustainable food yard utilization program (P2L) at KWT Jati Mandiri, Keban Jati Village, Ulu Manna District, South Bengkulu Regency. The number of recipients of the P2L program is 30 people. Sampling was carried out by census of recipients of the P2L program. The data collected in the form of the characteristics of program participants, aspects of targeting accuracy, aspects ofsocialization, aspects of mentoring, and aspects of achieving program goals using questionnaires. Data analysis was done descriptively. The results showed that the P2L program at KWT Jati Mandiri was very effective from the aspect of targeting accuracy, socialization, and program assistance, but less effective from the aspect of achieving program goals.